PUBLIC OPINION ON MENTAL HEALTH ILLNESS WITH SPECIAL REFERENCES TO CHENNAI - Balasubramanian, Sarnitha (International Journal of Psychosocial Rehabilitation, 2020)
Mental disorder, also called mental health illness. Mental illness has been a major problem for most of them globally. WHO (World Health Organization) takes necessary steps to improve the mental health by creating awareness globally. The objectives of this research are to identify the difference between the opinion on mental illness and gender of the respondents and to analyze the association between the major cause of mental illness and occupation of the respondents. The researcher has used descriptive method and convenient sampling method for the research. 1540 responses were collected. Dependent variables are mental illness, causes, treatment, psychotherapy, medication, advice, criticism, support group and exercise. Independent sample t-test, chi square and ANOVA are the research tools used in this research. From the research, it was found that the mental illness depends on the gender of the respondent and the causes of the mental illness are influenced by the occupation of the respondents.Researcher also suggests that an individual's biological, psychological and social elements can play an important part in their mental health.